O problema da constituição da liberdade em Hannah Arendt - Almeida, Rodrigo Moreira de (2012)
This dissertation approaches what is called the problem of the constitution of freedom in Hannah Arendt s political thought. Such problem presents itself in the form of a tension between the concern to think upon, on one hand, the action, power, and political freedom that are coeval, as spontaneous, indeterminate, innovative and possessing an extraordinary dimension; and, on the other hand, the necessary stability and delimitation of a political body based on normative elements, such as laws, institutions, constitutions, and an instance of authority and legitimacy that ensure some continuity to the public sector on the potential arbitrariness and limitlessness that freedom brings with it. This problem is articulated through the definition and specification, in the work of Arendt, of the relationship, apparently paradoxical, between the concepts of power, action and freedom, on the one hand, and on the other, the notions of law, constitution and authority. The issues raised are: 1. How does Arendt reconcile and balance the unpredictability, spontaneous and uncertain character of her concept of action with stabilizing and limiting aspects of the notions of law and constitution? 2. What elements of her theory help to think of normative principles of authority and legitimacy in the secular context? 3. And finally, how is it possible to think on lines of continuity between the constituent/founder dimension of power, which is essentially indeterminate and extraordinary, and constituted power? The hypotheses proposed are: 1 Arendt seeks a republican conception of law, strongly inspired by the Roman lex, which further emphasizes the directive-relational dimensions of the law than the mandatory and coercive idea. The author highlights the importance that the law and institutions are the result of the political and plural action of people, and that they are also linked to it, and that they are not imposed by a superior and autonomous legal rationality. She seeks, therefore, to overcome the traditional dichotomy between law and freedom by indicating a complementarity and interdependence between the constituent and constituted spheres. 2 The author constitutes elements to think on a new concept of authority, without resorting to transcendent and absolute elements as a normative source of legitimacy for secular republics, on one hand, in her theory of promises based on commitments and mutual guarantees that people establish with each other, and, on the other hand, on the complementary notion of immanent principles of action to the constituting act shared by a people, such as freedom, equality, and plurality, which could be incorporated into the constitutional document because they have a normative value sanctioned by people themselves. 3 - Finally, it is noted that Arendt seeks a republican notion of constitution, largely inspired by the American constitutionalism and by the federated republic model, the form of government that most fit to welcome and constitute public liberty.